2022
DOI: 10.3920/jaan2021.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytase supplementation on plasma and organ myo-inositol content and erythrocyte inositol phosphates as pertaining to breast meat quality issues in chickens

Abstract: ‘Woody breast’ (WB) and ‘white striping’ in broiler meat is a global problem. With unknown etiology, WB negatively impacts bird health, welfare and is a significant economic burden to the poultry industry. New evidence has shown that WB is associated with dysregulation in systemic and breast muscle-oxygen homeostasis, resulting in hypoxia and anaemia. However, it has been observed that phytase (Quantum Blue (QB) a modified, E. coli-derived 6-phytase) super dosing can reverse dysregulation of muscle-oxygen home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The tissue inositol phosphates ( Fig 1A and 1B ) are similar to those identified in avian erythrocytes [ 20 , 41 , 42 ]. Thus, despite clear impact of dietary phytase on inositol phosphates in gizzard and ileal content, and on tissue inositol phosphates, the tissue isomers (of inositol phosphates) are phosphorylated in positions not expected from phytate degradation by Quantum Blue or endogenous feed phytase.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The tissue inositol phosphates ( Fig 1A and 1B ) are similar to those identified in avian erythrocytes [ 20 , 41 , 42 ]. Thus, despite clear impact of dietary phytase on inositol phosphates in gizzard and ileal content, and on tissue inositol phosphates, the tissue isomers (of inositol phosphates) are phosphorylated in positions not expected from phytate degradation by Quantum Blue or endogenous feed phytase.…”
Section: Discussionsupporting
confidence: 65%
“…One objective of this study was to investigate the effect of the addition of dietary phytase on the inositol phosphate levels observed in poultry tissues. Previous studies have identified changes in plasma inositol levels in relation to changes in gizzard and ileal phytate hydrolysis [ 9 , 20 , 27 ], but have been unable to access tissue inositol phosphates by commonly used analytical methods. Consequently, the inositol phosphate profile of different tissues is undefined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations